(untitled) (Fiep Bulletin - online, 2015)
The objective of this study was to analyse the effects of a Body Pump program on antropometric and body composition variables of womans. Subjects were 10 womans, aged 20- 30 years old, and enrolled on a regular gym Mobi Dick. Stature and body mass, perimeters ( adomen at umbilicus and wais level, buttock, thigh and calf); sum of total skinfolds and limbs skinfolds ( upper and lower limb skinfolds). The % fat were estimated accordingly to Jackson & Pollock (1983) equations. Subjects were pre-and-pos evaluated after 32 Body Pump classes that met twice times a week for about 50 minutes each. Descriptive statistics and a Stundent dependent t-test were used for data interpretation. It was conclude that Body Pump training significantly promoved reduction (p<0,05) on total sum of skinfolds.